Case report: Diagnostic clues for anti-3-hydroxy-3-methylglutaryl-coenzyme A reductase myopathy in pediatric patients - Watanuki, Keisuke; Koga, Hiroshi (Frontiers in Pediatrics, 2023)
Introduction: Anti-3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) myopathy is a recently recognized pathology, but appears less common in children and the characteristics of pediatric cases remain unclear. Case Report: We report a pediatric case of anti-HMGCR myopathy accompanied by skin rash. Motor function and serum creatine kinase level normalized after combinational treatment including early intravenous immunoglobulin, methotrexate, and corticosteroid. Literature Review: We searched PubMed and identified reports with detailed clinical information of 33 pediatric patients <18 years old with anti-HMGCR myopathy. Among these 33 patients and our own case, skin rash and maximum serum creatine kinase level >5000 IU/L were observed in 44% (15 patients) and 94% (32 patients), respectively. Skin rash was present in 15 of the 22 patients (68%) ≥7 years old and none of the 12 patients (0%) <7 years old. Among the 15 patients with skin rash, 12 (80%) presented with erythematous rash. Conclusion: Erythematous skin rash may offer a clue to the diagnosis of anti-HMGCR myopathy in children with muscle weakness and serum creatine kinase level >5000 IU/L in the absence of other myositis-specific antibodies, particularly in patients ≥7 years old. Our results suggest the importance of early anti-HMGCR testing in pediatric patients with these manifestations.